2015
DOI: 10.5539/ass.v11n18p311
|View full text |Cite
|
Sign up to set email alerts
|

Agency Costs, Corporate Governance and Ownership Concentration: The Case of Agro-industrial Companies in Indonesia

Abstract: This study aims to investigate determinants of agency costs on agro-industrial firms that are listed in the Indonesian Stock Exchange (IDX). Modeling of agency costs is analyzed by performing regression analysis of panel data. This study employs secondary data of 54 companies from year 2010 to 2013. The results show that agency costs are affected by the effectiveness of good governance mechanism, especially the function of board of directors (BOD) and board of commissioners (BOC) in conducting their duties, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
3
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 25 publications
2
18
3
12
Order By: Relevance
“…The more payment for loan means lower return for shareholders. It is parallel with the findings of Hastori et al [2], which said that there was a significantly negative relation between dividend payout policy and agency costs while leverage had significantly positive influence towards agency cost. Agency problem may occur when dividend paid is smaller because of higher payment for loan or higher amount of retained earnings.…”
Section: Introductionsupporting
confidence: 79%
“…The more payment for loan means lower return for shareholders. It is parallel with the findings of Hastori et al [2], which said that there was a significantly negative relation between dividend payout policy and agency costs while leverage had significantly positive influence towards agency cost. Agency problem may occur when dividend paid is smaller because of higher payment for loan or higher amount of retained earnings.…”
Section: Introductionsupporting
confidence: 79%
“…Agency cost can be measured with different tools, most important are asset utilization ratio (Rashid, 2013), expense ratio (Wellalage & Locke, 2012), free cash flow interaction (Henry, 2010), dividend payout ratio (Wellalage & Locke, 2011) and Tobin's Q (El-Faitouri, 2014). Agency problems can be controlled with the help of many corporate governance attributes like managerial ownership (Rashid, 2015), executive compensation (Core, Holthausen & Larcker, 1999), debt (Paterson, 2016), or Board of directors (Hastori, Siregar, Sembel & Maulana, 2015) and dividends (Park, 2009).…”
Section: Background and Hypothesis Developmentmentioning
confidence: 99%
“…This will be measured by taking the natural logarithm of the total number of directors in the board. Gul, Sajid, Razzaq and Afzal (2012) and Hastori et al (2015) concluded that the size of the board helped in controlling agency cost.…”
Section: Size Of Boardmentioning
confidence: 99%
“…And the benefits assigned to the major shareholders are far greater than their supervision costs, so they have more impetuses to manage managers, giving full play to their functions, reducing managers` personal profit behaviors, and more easily through the shareholders to reach a consensus, thereby improving corporate performance. And Hastori H (2015) investigated determinants of agency costs , found that ownership concentration affected agency costs in vary [5]. H3:The proportion of the top ten shareholders is positively related to the corporate performance.…”
Section: The Impact Of the Equity Structure On The Corporate Performancementioning
confidence: 99%